Deoxynivalenol and nivalenol in commercial wheat grain related to Fusarium head blight epidemics in southern Brazil - Del Ponte, Emerson Medeiros (2012)
A three-year (2006–2008) survey on commercial wheat grain was conducted aimed at quantifying the intensity of Fusarium head blight epidemics related to kernel quality and levels of deoxynivalenol (DON) and nivalenol (NIV). Grain samples, obtained from 38 municipalities throughout the state of Rio Grande do Sul, Brazil, were assessed visually for Fusarium-damaged kernels (FDK) and chemically using liquid chromatography–mass spectrometry (LC–MS/MS). Overall FDK mean levels were 15.5%, not differing among the years. Co-contamination was predominant (59/66) across samples and overall mean levels of DON and NIV were 540 and 337 lg/kg, respectively. When the levels of both mycotoxins were added together (DON + NIV), a higher correlation with FDK was found (R = 0.36, P < 0.01), compared to single toxin data. For the first time, the presence of NIV in levels comparable to DON is reported from a multi-year regional epidemiological survey in the country which should be of concern to the small grains industry.